Can extreme rainfall trigger democratic change? The role of flood-induced corruption - Rahman, Muhammad Habibur; Anbarci, N.; Bhattacharya, P.S.; Ulubaşoğlu, M.A. (SPRINGER, 2017)
© 2017, Springer Science+Business Media New York.